Religion, Öffentlichkeit, Moderne: Transdisziplinäre Perspektiven (unter Mitarbeit von Martin Breul) - Könemann, Judith; Wendel, Saskia; Breul, Martin (Religionswissenschaft, 2016)
What is the role of religious groups and their (religious) convictions in the public sphere of the liberal late modern society? The contributions to this volume look at the complex web of religion, public sphere, and modernity from perspectives of theology, philosophy of religion, sociology of religion, and political philosophy. They aim at a rational and up-to-date characterization of the meaning that religious groups and traditions bear for late modern societies